1975
DOI: 10.1530/acta.0.0790474
|View full text |Cite
|
Sign up to set email alerts
|

Acute Suppressive Effect of Human Growth Hormone on Basal Insulin Secretion in Man

Abstract: The acute effects of human growth hormone (GH) on the basal levels of glucose and insulin in blood were investigated in 11 healthy men. GH doses of 5, 10, 20, and 40 \g=m\g/kgbody weight were given iv as a constantrate infusion over 30 min, and resulted in peak hormone levels (30 min) of 20.5 \ m=+-\ 1.0, 48.5 \ m=+-\ 2.2, 108.2 \ m=+-\ 4.5, and 229.2 \ m=+-\ 14.6 ng/ml, respectively. There was a small (max 9.8 \ m=+-\2.6 %) but significant decrease in the blood glucose level, observed already at 15 min after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1978
1978
1991
1991

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Growth hormone also has multiple effects on glucose kinetics, varying with the duration of exposure and the time interval after exposure. Several investigators have demonstrated that growth hormone has early insulin-like effects [36][37][38]. However, insulin antagonistic effects of the hormone can be seen 2-12 h after growth hormone administration [39][40][41], and could exert a delayed effect on glucose metabolism since even transient elevations of growth hormone have been shown to impair even transient elevations of growth hormone have been shown to impair glucose tolerance for at least 5 h [41].…”
Section: Discussionmentioning
confidence: 99%
“…Growth hormone also has multiple effects on glucose kinetics, varying with the duration of exposure and the time interval after exposure. Several investigators have demonstrated that growth hormone has early insulin-like effects [36][37][38]. However, insulin antagonistic effects of the hormone can be seen 2-12 h after growth hormone administration [39][40][41], and could exert a delayed effect on glucose metabolism since even transient elevations of growth hormone have been shown to impair even transient elevations of growth hormone have been shown to impair glucose tolerance for at least 5 h [41].…”
Section: Discussionmentioning
confidence: 99%